Conditioned place avoidance is associated with a distinct hippocampal phenotype, partly preserved pattern separation, and reduced reactive oxygen species production after stress. (17th February 2023) - Kelley, D. Parker; Albrechet‐Souza, Lucas; Cruise, Shealan; Maiya, Rajani; Destouni, Aspasia; Sakamuri, Siva S. V. P.; Duplooy, Alexander; Hibicke, Meghan; Nichols, Charles; Katakam, Prasad V. G.; Gilpin, Nicholas W.; Francis, Joseph
Abstract: Stress is associated with contextual memory deficits, which may mediate avoidance of trauma‐associated contexts in posttraumatic stress disorder. These deficits may emerge from impaired pattern separation, the independent representation of similar experiences by the dentate gyrus‐Cornu Ammonis 3 (DG‐CA3) circuit of the dorsal hippocampus, which allows for appropriate behavioral responses to specific environmental stimuli. Neurogenesis in the DG is controlled by mitochondrial reactive oxygen species (ROS) production, and may contribute to pattern separation. In Experiment 1, we performed RNA sequencing of the dorsal hippocampus 16 days after stress in rats that either develop conditioned place avoidance to a predator urine‐associated context (Avoiders), or do not (Non‐Avoiders). Weighted genome correlational network analysis showed that increased expression of oxidative phosphorylation‐associated gene transcripts and decreased expression of gene transcripts for axon guidance and insulin signaling were associated with avoidance behavior. Based on these data, in Experiment 2, we hypothesized that Avoiders would exhibit elevated hippocampal (HPC) ROS production and degraded object pattern separation (OPS) compared with Nonavoiders. Stress impaired pattern separation performance in Non‐Avoider and Avoider rats compared with nonstressed Controls, but surprisingly, Avoiders exhibited partly preserved pattern separation performance and significantly lower ROS production compared with Non‐Avoiders. Lower ROS production was associated with better OPS performance in Stressed rats, but ROS production was not associated with OPS performance in Controls. These results suggest a strong negative association between HPC ROS production and pattern separation after stress, and that stress effects on these outcome variables may be associated with avoidance of a stress‐paired context. Abstract : Divergent adaptive responses to predator odor stress at the molecular, functional, and behavioral levels. Contextual avoidance is associated with metabolic, mitochondrial and anabolic transcriptional adaptations, and partly preserved pattern separation in the dorsal hippocampus. Non‐Avoiders show elevated ROS and total loss of dorsal hippocampal pattern separation. ROS production correlates with pattern separation performance in Stressed (Avoider + Non‐Avoider), but not Control rats.